Faktor-faktor yang Memengaruhi Perilaku Knowledge Sharing di Kalangan Software Developer di Indonesia - Ringgi Cahyo Dwiputra; Ariq Naufal Satria; Dana Indra Sensuse; Sofian Lusa; Damayanti Elisabeth (The Indonesian Journal of Computer Science, 2024)
Knowledge sharing is a crucial element for enhancing efficiency in the software development process. However, it proves to be a challenging and complicated task in practice, particularly due to the insufficient knowledge and experience of software developers. The aim of this research is to pinpoint key success factors in knowledge sharing behavior among software developers. Based on Social Cognitive Theory (SCT), the research divides components into three categories: behavioral, environmental, and personal. For a more complete picture, an additional organizational aspect is included. The partial least squares structural equation model was utilized to analyze the data collected from 198 software developers in Indonesia. The findings reveal that motivation, trust, social interaction, organizational culture, reward, and management support positively influence knowledge sharing behavior, while geographical distance has a negative impact. This research contributes by filling a gap in previous research that utilized SCT, broadening the model to identify determinant factors explaining knowledge sharing behavior within an organizational context.